Association Between Metabolic Dysfunction-Associated Fatty Liver Disease and Cardiovascular Risk in Patients With Rheumatoid Arthritis: A Cross-Sectional Study of Chinese Cohort - Zou, Yao-Wei; Li, Qian-Hua; Gao, Jing-Wei; Pan, Jie; Ma, Jian-Da; Chen, Le-Feng; Lin, Jian-Zi; Mo, Ying-Qian; Zhang, Xue-Pei; Liu, Pin-Ming; Dai, Lie (Frontiers in Cardiovascular Medicine, 2022)
Background: The nomenclature from non-alcoholic fatty liver disease (NAFLD) to metabolic dysfunction-associated fatty liver disease (MAFLD) is considered to identify more cardiovascular disease (CVD) risks in the general population. Patients with rheumatoid arthritis (RA) carry an excess risk for CVD. However, the prevalence of MAFLD and its relationship with CVD risks in RA have not been reported. Methods: This cross-sectional study retrospectively analyzed clinical data from a Chinese RA cohort. MAFLD was diagnosed according to the criteria proposed by an international expert panel from 22 countries in 2020. CVD risk in RA patients was estimated by the Prediction for Atherosclerotic Cardiovascular Disease Risk in China with a 1.5 multiplication factor. Results: Among 513 included RA patients, 78.4% were female and the mean ± SD age was 51.8 ± 12.6 years. The prevalence of MAFLD was 21.4%. There were 10.9% RA patients concomitated with CVD events and 32.4% with a high estimated 10-year CVD risk. Besides a higher liver fibrosis score and a higher ratio of advanced fibrosis, RA patients with MAFLD had a higher rate of CVD events (17.3% vs. 9.2%), and a higher proportion of high estimated 10-year CVD risk (55.5% vs. 26.1%) than those without. Multivariate logistic regression analysis showed that MAFLD was associated with an increase in CVD events [adjusted odds ratio (AOR) = 2.190, 95% CI 1.135-4.227] and high estimated 10-year CVD risk (AOR = 2.483, 95% CI 1.412-4.365, all p < 0.05). Conclusions: MAFLD was associated with increased CVD risk in RA patients, which implies the importance of early detection and management of MAFLD in RA patients.